2007
DOI: 10.1529/biophysj.106.102947
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Extracellular Ion Gradients from Single Channels with Ion-Selective Microelectrodes

Abstract: Under many different conditions activated plasma membrane ion channels give rise to changes in the extracellular concentration of the permeant ion(s). The magnitude and duration of these changes are dependent on the electrochemical driving force(s) on the permeant ion(s) as well as conductance, open time, and channel density. We have modeled the change in the extracellular [K+] due to efflux through Ca2+-activated K+ channels, mSlo, to determine the range of parameters that would give rise to measurable signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…4 answers this question and illustrates the recording of single potassium channels. (33,34) Using the CHO heterologous system we also demonstrated that the microelectrode acts as an ion-trap, amplifying the signal from the channel. Obtaining a rapid response potas-sium electrode did require design changes in both the electrode body and the ionophore cocktail.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…4 answers this question and illustrates the recording of single potassium channels. (33,34) Using the CHO heterologous system we also demonstrated that the microelectrode acts as an ion-trap, amplifying the signal from the channel. Obtaining a rapid response potas-sium electrode did require design changes in both the electrode body and the ionophore cocktail.…”
mentioning
confidence: 86%
“…(28,29) Potentiometric applications have taken advantage of the several excellent ionselective cocktails available commercially, notably for hydrogen, potassium and calcium, with modified cocktails being developed specifically for self-referencing detection of chloride or sodium (32) and rapid response time potassium sensors. (33,34) Amperometric detection depends on reduction/oxidation chemistry. Detection of nitric oxide, oxygen and hydrogen peroxide are now routine applications (sensor fabrication (29,35) ).…”
Section: Measuring Chemical Signatures In Vitromentioning
confidence: 99%
“…The recent use of this design was able to resolve the transient changes (1 -2 s duration) of Ca 2þ and H þ in the extracellular spaces of the brain [8 -10]. We have employed the use of shorter columns to capture rapid K þ changes due to efflux through single Ca 2þ -activated K þ channels [11,12].…”
Section: Short Response Times With Ismsmentioning
confidence: 99%
“…Microelectrodes were constructed with short columns (ca. 9 mm) of a mechanically stable K þ increases of 1 -10 mM and fit a diffusion model when response time and ion trapping by the ISM are considered [11,12]. In Figure 3A and B the rapid transients appear as spikes.…”
Section: Measurement Of Single Channel Gradientsmentioning
confidence: 99%
See 1 more Smart Citation